Effects of Herpes Simplex Virus Amplicon Transduction on Murine Dendritic Cells - Chiu, Yahui Grace (Mary Ann Liebert, Inc., 2009)
The herpes simplex virus (HSV)-based amplicon is a versatile vaccine platform that has been preclinically vetted as a gene-based immunotherapeutic for cancer, HIV, and neurodegenerative disorders. Although it is well known that injection of dendritic cells (DCs) transduced ex vivo with helper virus-free HSV amplicon vectors expressing disease-relevant antigens induces antigen-specific immune responses, the cellular receptor(s) by which the amplicon virion gains entry into DCs, as well as the effects that viral vector transduction impinges on the physiological status of these cells, is less understood. Herein, we examine the effects of amplicon transduction on mouse bone marrow-derived DCs. We demonstrate that HSV-1 cellular receptors HveC and HveA are expressed on the cell surface of murine DCs, and that HSV amplicons transduce DCs at high efficiency (>90%) with minimal effects on cell viability. Transduction of dendritic cells with amplicons induces a transient DC maturation phenotype as represented by self-limited upregulation of MHCII and CD11c markers. Mature DCs are less sensitive to HSV amplicon transduction than immature DCs regarding DC-related surface marker maintenance. From this and our previous work, we conclude that HSV amplicons transduce DCs efficiently, but impart differential and transient physiological effects on mature and immature DC pools, which will facilitate fine-tuning of this vaccination platform and further exploit its potential in immunotherapy.